2004
DOI: 10.1021/es0490830
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers Contamination of United States Food

Abstract: Elevated levels of polybrominated diphenyl ethers (PBDEs), a type of brominated flame retardant, were recently detected in U.S. nursing mothers' milk. These halogenated compounds chemically and toxicologically resemble others such as polychlorinated biphenyls (PCBs), whose route of intake is almost exclusively through food of animal origin. This study is the first to report the levels of PBDEs in U.S. foods in a market basket survey of 30 food types (total of 32 food samples) from three major supermarket chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
125
7
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(151 citation statements)
references
References 31 publications
16
125
7
3
Order By: Relevance
“…Moreover, the quantity of rice intake (310 g day − 1 ) was highest in these selected foods by local residents, the two factors can explain the finding that the highest PBDEs intake through rice consumption observed in the study. PBDE47 was found to be the most predominant congener for the total PBDEs intake in the study sites, similar findings were also reported in Finnish, American and Swedish market baskets study on dietary intake (Kiviranta et al, 2004;Schecter et al, 2004;Darnerud et al, 2006), for example, PBDE47 accounted for 48% of the total PBDEs intake in Finnish study. PBDE47 was almost detected in all of the selected food samples, which can support the finding that PBDE47 was the primary intake contributor for the total PBDEs intake in the study.…”
Section: Pbdessupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the quantity of rice intake (310 g day − 1 ) was highest in these selected foods by local residents, the two factors can explain the finding that the highest PBDEs intake through rice consumption observed in the study. PBDE47 was found to be the most predominant congener for the total PBDEs intake in the study sites, similar findings were also reported in Finnish, American and Swedish market baskets study on dietary intake (Kiviranta et al, 2004;Schecter et al, 2004;Darnerud et al, 2006), for example, PBDE47 accounted for 48% of the total PBDEs intake in Finnish study. PBDE47 was almost detected in all of the selected food samples, which can support the finding that PBDE47 was the primary intake contributor for the total PBDEs intake in the study.…”
Section: Pbdessupporting
confidence: 87%
“…These findings in the last study tend to support the notion that PBDE209 through complex biogeochemical processes could eventually be bioaccumulated in food chains. In their study, Schecter et al (2004Schecter et al ( , 2006 made a similar observation finding that PBDE209 also detected in many meat products in US (such as chicken breast, and pork). What's more, PBDE209 was a major contributor in some food supplies (e.g.…”
Section: Pbdessupporting
confidence: 55%
“…These levels were also one to two orders of magnitude higher than PBDE concentrations (564 ng/g lipid weight) examined in eggs from the e-waste recycling site in Southeast China (Qin et al, 2011), two to three orders of magnitude greater than those (7.8 ng/g lipid weight) detected in the home-produced eggs from Belgian (Covaci et al, 2009), and three to four orders of magnitude greater than the reported levels (b1.5 ng/g lipid weight) in eggs from markets of Spain (Bocio et al, 2003), Sweden (Darnerud et al, 2006), Belgian (Voorspoels et al, 2007), and USA (Schecter et al, 2004(Schecter et al, , 2006. The results suggested that home-produced eggs from the e-waste recycling sites have been heavily polluted by PBDEs, because of the primitive recycling procedures without adequate measures of protecting environmental and human health (Wu et al, 2008).…”
Section: Levelsmentioning
confidence: 73%
“…Additionally, they are considered to be a good indicator of ambient persistent organic pollutants levels (Windal et al, 2009). However, the contribution of eggs to dietary exposure of HFRs is generally ignored and there are only a few reports on HFRs occurrence in eggs (Bocio et al, 2003;Covaci et al, 2009;Darnerud et al, 2006;Qin et al, 2011;Rawn et al, 2011;Schecter et al, 2004Schecter et al, , 2006Voorspoels et al, 2007). Nevertheless, the available data on HFRs in eggs generally concerns commercially produced eggs (based on market basket surveys), few study results are reported HFRs in home-produced eggs (Covaci et al, 2009;Fernandes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, with regard to occupational exposure, in a group of computer dismantlers, serum levels of PBDEs were 26 ng/g, compared to 3.3 ng/g in a reference group of hospital cleaners (Sjodin et al 1999). Among foods, fish has the highest content of PBDEs, followed by meat and diary products, with meat estimated to be the major source of PBDEs in the U.S. diet (Schecter et al 2004;Hites et al 2004;Jones-Otazo et al 2005;Schecter et al 2006a). In a small study, vegetarians (vegans) were found to have somewhat lower plasma levels of PBDEs (range 12.4 -127 ng/g lipid) than the general U.S. population (4 -366 ng/g lipid) (Schecter et al 2006b).…”
Section: Human Exposure and Body Burdenmentioning
confidence: 99%